Leadership Style and Performance in Higher Education Institutions (PHEI): the Mediating Role of Organizational Culture - Suparman, Dadang; Rahayu, Siti Widhiyanti; Firmansyah, Deri (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this study is to examine the relationship between Leadership Style (LS) and Performance in Higher Education Institution (PHEI), the mediating effect of Organizational Culture (OC) on the relationship between the two is examined. Quantitative research approach with survey type. Descriptive and verifiable analyses were carried out to confirm and test the predictive causality of the constructed model. The total sample was 43 respondents selected using a purposive sampling approach. Path analysis is applied to analyze data in the research model. Forecasting with a regression approach, the process SPSS macro model was adopted to test the mediation effect. The estimation of the mediation effect was carried out by the Sobel test. The findings of the leadership style research have a positive and significant direct effect on the performance of higher education institutions, leadership style has a positive and significant effect on organizational culture, organizational culture has a positive and significant effect on the performance of higher education institutions. Organizational culture has a positive and significant indirect effect on the influence of leadership style on the performance of higher education institutions, there is a strong mediation effect of organizational culture compared to the direct effect of leadership style on the performance of higher education institutions. Research contributions, implications and recommendations are explained in this paper.